Composite gas diffusion layer with corrosion resistance and preparation method and application thereof
By disproportionate reaction between alkaline metal molten salt and chromium-containing active substances in the composite gas diffusion layer, a corrosion-resistant chromium carbide coating is formed, which solves the problem of easy corrosion of the composite gas diffusion layer, and improves the porosity and extends the The service life of fuel cells.
Patent Information
- Application Number
- CN202411407294.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-21
AI Technical Summary
The composite gas diffusion layer is susceptible to carbon oxidation corrosion in proton exchange membrane fuel cells, which affects its service life. At the same time, the application of corrosion-resistant layer will reduce porosity.
By mixing the alkaline metal molten salt and the chromium-containing active substance, a disproportionation reaction is carried out to form a chromium carbide coating with corrosion resistance, and the porosity is adjusted through the diffusion of divalent chromium ions with carbon fibers and carbon nanotubes.
The corrosion resistance and porosity of the composite gas diffusion layer are synchronized, extending the service life of the fuel cell and maintaining the water management capabilities.
Smart Images

Figure CN119495753A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite gas diffusion layers, and in particular to a composite gas diffusion layer with corrosion resistance, a preparation method thereof, and an application thereof. Background Art
[0002] The composite gas diffusion layer plays the role of reactant transport, water transport, electron conduction, heat conduction and mechanical support in the entire proton exchange membrane fuel cell. However, since the composite gas diffusion layer is mainly composed of carbon fiber and carbon black, the disadvantage of these raw materials is that they are easily subject to carbon oxidation corrosion, and the carbon of carbon fiber and carbon black will undergo oxidation reaction in an acidic environment; in addition, during the normal power generation process of the proton exchange membrane fuel cell, the carbon of carbon fiber and carbon black will also undergo oxidation reaction; and when the fuel is insufficient or the start-stop operation is performed, this will cause the electrode potential of the proton exchange membrane fuel cell to increase sharply, causing the electrode potential of the proton exchange membrane fuel cell to be at a higher level, and the proton exchange membrane fuel cell at a higher level will cause the carbon of the carbon fiber and carbon black to be severely oxidized and corroded, which will cause irreversible damage to the proton exchange membrane fuel cell and affect the service life of the proton exchange membrane fuel cell. In addition, after the carbon of carbon fiber and carbon black is oxidized and corroded, the thickness and mechanical strength of the composite gas diffusion layer will decrease, and as the oxidation and corrosion of carbon intensifies, the carbon of carbon fiber and graphite in the central area of the gas diffusion layer will gradually be lost or degraded to form large pores in the central area of the gas diffusion layer, thereby affecting the pore size distribution of the gas diffusion layer, and even causing the pore structure of the composite gas diffusion layer to collapse, reducing the water management capacity of the composite gas diffusion layer. Therefore, the limiting potential and acidic environment of the proton exchange membrane fuel cell will make the degradation of the composite gas diffusion layer inevitable.
[0003] Although corrosion-resistant layers are currently coated on the surface of the composite gas diffusion layer of proton exchange membrane fuel cells to reduce or even avoid carbon corrosion of carbon fibers and carbon black in the composite gas diffusion layer, these corrosion-resistant layers will cover most of the pores in the microporous layer, affecting the porosity of the composite gas diffusion layer, thereby reducing the water management capacity of the composite gas diffusion layer. Summary of the invention
[0004] The present application provides a composite gas diffusion layer with corrosion resistance and a preparation method and application thereof, in order to solve the following technical problem: how to simultaneously improve the corrosion resistance and porosity of the composite gas diffusion layer.
[0005] In a first aspect, the present application provides a method for preparing a composite gas diffusion layer having corrosion resistance, wherein the method is directed to a crude gas diffusion layer product, wherein the crude gas diffusion layer product comprises a base layer and a microporous layer covering the surface of the base layer, and the method comprises:
[0006] Mixing alkaline metal molten salt and chromium-containing active material to obtain mixed active alkaline metal molten salt;
[0007] preheating the microporous layer to obtain a preheated microporous layer;
[0008] Heating the mixed active alkaline metal molten salt in a vacuum environment to obtain a mixed active melt;
[0009] immersing the preheated microporous layer in the mixed active melt to perform a disproportionation reaction to obtain a crude composite gas diffusion layer with an anti-corrosion coating;
[0010] Cooling the crude composite gas diffusion layer with the anti-corrosion coating and then purifying it to obtain a composite gas diffusion layer;
[0011] Wherein, the raw material of the microporous layer includes carbon nanotubes, and the raw material of the base layer includes carbon fibers;
[0012] The weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance satisfy the relationship: m1:m2=(5:1)-(10:1).
[0013] Optionally, the chromium-containing active material includes metallic chromium and / or chromium fluoride, and the alkaline metal molten salt includes a chloride of an alkaline metal.
[0014] Optionally, the chromium-containing active substance includes metallic chromium and chromium chloride, and the amount n1 of the metallic chromium and the amount n2 of the chromium chloride satisfy the relationship: n1:n2≥8:1.
[0015] Optionally, the alkaline metal includes sodium and / or lithium.
[0016] Optionally, the raw materials of the microporous layer also include carbon black particles and pore-forming agents, and the weight m3 of the carbon black particles, the weight m4 of the carbon nanotubes and the weight m5 of the pore-forming agent satisfy the relationship: (m3+m4):m5=(4.7-6.3):1.
[0017] Optionally, the weight m5 of the carbon nanotubes and the weight m3 of the carbon black particles satisfy the relationship: m5:m3=1:(8.5-10.5).
[0018] Optionally, the heating temperature is 600° C. to 900° C., and the heating time is 0.5 h to 1 h.
[0019] Optionally, the cooling end point temperature is ≤30°C.
[0020] In a second aspect, the present application provides a composite gas diffusion layer with corrosion resistance, wherein the composite gas diffusion layer is prepared by the preparation method described in the first aspect.
[0021] Optionally, the composite gas diffusion layer comprises a base layer, a microporous layer and an anti-corrosion layer, wherein the microporous layer covers the surface of the base layer, and the anti-corrosion layer covers the surface of the microporous layer.
[0022] In a third aspect, the present application provides a method for preparing the composite gas diffusion layer according to the second aspect, the method comprising:
[0023] The base layer is impregnated with a water repellent solution, and then the impregnated base layer is dried to obtain a pre-treated base layer;
[0024] The carbon black particles, carbon nanotubes and pore-forming agent are mixed, and then the mixed mixture is stirred and ultrasonically dispersed to obtain a primary microporous layer slurry;
[0025] Mixing the water repellent and the primary microporous layer slurry, and then stirring and ultrasonically dispersing the mixed mixture to obtain a microporous layer slurry;
[0026] Applying the microporous layer slurry to the surface of the pretreated substrate layer, and then calcining the pretreated substrate layer coated with the microporous layer slurry to obtain a crude gas diffusion layer;
[0027] The crude gas diffusion layer is processed using the preparation method described in the first aspect to obtain a composite gas diffusion layer.
[0028] Optionally, the weight m6 of the water repellent and the weight m5 of the pore-forming agent satisfy the relationship: m6:m5=(2.4-3.7):1.
[0029] Optionally, the drying temperature is 45° C. to 55° C., the drying time is 15 min to 20 min, and the immersion time is 5 min to 15 min.
[0030] In a fourth aspect, the present application provides a membrane electrode, which includes the composite gas diffusion layer described in the second aspect.
[0031] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0032] The embodiment of the present application provides a method for preparing a composite gas diffusion layer with corrosion resistance. The preparation method is for a crude gas diffusion layer, and the crude gas diffusion layer includes a base layer and a microporous layer covering the surface of the base layer. The preparation method includes: mixing an alkaline metal molten salt and a chromium-containing active substance to obtain a mixed active alkaline metal molten salt; preheating the microporous layer to obtain a preheated microporous layer; heating the mixed active alkaline metal molten salt in a vacuum environment to obtain a mixed active melt; immersing the preheated microporous layer in the mixed active melt to perform a disproportionation reaction to obtain a crude composite gas diffusion layer with an anti-corrosion coating; cooling the crude composite gas diffusion layer with an anti-corrosion coating, and then purifying to obtain a composite gas diffusion layer; wherein the raw material of the microporous layer includes carbon nanotubes; the weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance satisfy the relationship: m1:m2=(5:1)~(10:1). The weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance can satisfy the relationship: m1:m2=(5:1)~(10:1), which can promote the alkaline metal molten salt and the chromium-containing active substance to undergo sufficient disproportionation reaction on the surface of the preheated microporous layer to obtain a sufficient amount of divalent chromium ions. The sufficient amount of divalent chromium ions can effectively diffuse into the microporous layer and the base layer, and respectively form chromium carbide coatings with the carbon nanotubes in the microporous layer and the carbon fibers in the base layer. These chromium carbide coatings can effectively improve the corrosion resistance of the gas diffusion layer; in addition, when the divalent chromium ions and the carbon fibers in the base layer form the chromium carbide coatings and grow outward, the chromium carbide coatings will also be connected with the carbon nanotubes in the microporous layer to form a network structure of chromium carbides. These network structures of chromium carbides can adjust the porosity and pore size distribution of the microporous layer to avoid the formed chromium carbide coatings affecting the pores of the microporous layer, thereby improving the porosity of the gas diffusion layer; therefore, the preparation method can achieve the simultaneous improvement of the corrosion resistance and porosity of the composite gas diffusion layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0035] Figure 1 A schematic diagram of a method for preparing a corrosion-resistant composite gas diffusion layer provided in an embodiment of the present application;
[0036] Figure 2 A schematic flow chart of a method for preparing a composite gas diffusion layer provided in an embodiment of the present application;
[0037] Figure 3 A schematic diagram comparing initial performance polarization curves of the composite gas diffusion layer provided in Example 1, Example 2 and Comparative Example 1 of the present application;
[0038] Figure 4 This is a schematic diagram comparing the performance polarization curves of the composite gas diffusion layers provided in Example 1, Example 2 and Comparative Example 1 of the present application after 100 hours of durability treatment. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0040] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0041] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0042] Figure 1 A schematic flow chart of a method for preparing a corrosion-resistant composite gas diffusion layer provided in an embodiment of the present application is exemplarily shown;
[0043] like Figure 1 As shown, an embodiment of the present application provides a method for preparing a composite gas diffusion layer with corrosion resistance, the preparation method is for a crude gas diffusion layer, the crude gas diffusion layer includes a base layer and a microporous layer covering the surface of the base layer, the preparation method includes:
[0044] S1. The alkaline metal molten salt and the chromium-containing active substance are mixed to obtain a mixed active alkaline metal molten salt;
[0045] S2. preheating the microporous layer to obtain a preheated microporous layer;
[0046] S3. Heating the mixed active alkaline metal molten salt in a vacuum environment to obtain a mixed active melt;
[0047] S4. Immersing the preheated microporous layer in the mixed active melt to perform a disproportionation reaction to obtain a crude composite gas diffusion layer having an anti-corrosion coating;
[0048] S5. The crude composite gas diffusion layer having an anti-corrosion coating is cooled and then purified to obtain a composite gas diffusion layer;
[0049] Wherein, the raw material of the microporous layer includes carbon nanotubes, and the raw material of the base layer includes carbon fibers;
[0050] The weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance satisfy the relationship: m1:m2=(5:1)-(10:1).
[0051] The weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance may satisfy the relationship: m1:m2=5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.
[0052] It should be noted that the base layer can be carbon paper or carbon fiber cloth.
[0053] It should be noted that, in addition to carbon nanotubes, the raw material of the microporous layer may also be conductive carbon black material, such conductive carbon black material may be acetylene black, Vulcan XC-72 carbon black material, or Cabot BP2000 superconductive carbon black.
[0054] It should be noted that the preheating temperature may be 200°C, 205°C, 210°C, 215°C or 220°C.
[0055] It should be noted that the purification can be performed by using distilled water as a medium for cleaning under ultrasonic conditions to remove the impurity salt components on the surface of the crude composite gas diffusion layer, and then the cleaned crude composite gas diffusion layer is dried.
[0056] In some optional embodiments, the chromium-containing active material includes metallic chromium and / or chromium fluoride, and the alkaline metal molten salt includes a chloride salt of an alkaline metal;
[0057] In these embodiments, the chromium-containing active material may include metallic chromium and / or chromium fluoride, and the alkaline metal molten salt may include alkaline metal chloride, which can further promote the alkaline metal chloride and the chromium-containing active material to undergo a sufficient disproportionation reaction on the surface of the preheated microporous layer to obtain a sufficient amount of divalent chromium ions, and the sufficient amount of divalent chromium ions can be effectively diffused into the microporous layer and the base layer, and form a chromium carbide coating with the carbon nanotubes in the microporous layer and the carbon fibers in the base layer, respectively, to achieve a simultaneous improvement in the corrosion resistance and porosity of the composite gas diffusion layer.
[0058] In some optional embodiments, the chromium-containing active material includes metallic chromium and chromium chloride, and the amount n1 of the metallic chromium and the amount n2 of the chromium chloride satisfy the relationship: n1:n2≥8:1;
[0059] In these embodiments, the chromium-containing active material may include metallic chromium and chromium chloride, and the amount of metallic chromium n1 and the amount of chromium chloride n2 may satisfy the relationship: n1:n2≥8:1, which may promote the presence of sufficient zero-valent chromium and trivalent chromium in the chromium-containing active material, facilitate the subsequent complete disproportionation reaction between zero-valent chromium and trivalent chromium, so as to obtain sufficient divalent chromium ions, and the sufficient divalent chromium ions may be effectively diffused into the microporous layer and the base layer, and form chromium carbide coatings with the carbon nanotubes in the microporous layer and the carbon fibers in the base layer, respectively, so as to achieve the simultaneous improvement of the corrosion resistance and porosity of the composite gas diffusion layer.
[0060] In some optional embodiments, the alkaline metal includes sodium and / or lithium;
[0061] In these embodiments, the alkaline metal may include sodium and / or lithium, and the alkaline metals such as sodium or lithium can promote the disproportionation reaction to proceed sufficiently, thereby obtaining a sufficient amount of divalent chromium ions, and the sufficient amount of divalent chromium ions can be effectively diffused into the microporous layer and the base layer, and form a chromium carbide coating with the carbon nanotubes in the microporous layer and the carbon fibers in the base layer, respectively, to achieve a simultaneous improvement in the corrosion resistance and porosity of the composite gas diffusion layer.
[0062] It should be noted that, when the alkaline metal is sodium and lithium, the alkaline metal molten salt may be sodium chloride and lithium chloride, and the molar ratio of the sodium chloride to the lithium chloride may be 1:1.
[0063] In some optional embodiments, the raw materials of the microporous layer further include carbon black particles and a pore-forming agent, and the weight m3 of the carbon black particles, the weight m4 of the carbon nanotubes and the weight m5 of the pore-forming agent satisfy the relationship: (m3+m4):m5=(4.7-6.3):1;
[0064] In these embodiments, the raw materials of the microporous layer may also include carbon black particles and pore-forming agents, and the weight m3 of the carbon black particles, the weight m4 of the carbon nanotubes and the weight m5 of the pore-forming agent satisfy the relationship: (m3+m4):m5=(4.7-6.3):1, which can ensure that there are sufficient carbon black particles, carbon nanotubes and pore-forming agents in the microporous layer. Through the interaction of these three, not only the porosity of the microporous layer can be improved, but also the conductivity of the gas diffusion layer can be improved.
[0065] The weight m3 of the carbon black particles, the weight m4 of the carbon nanotubes and the weight m5 of the pore-forming agent satisfy the relationship: (m3+m4): m5=4.7:1, 4.8:1, 4.9:1, 5.0:1, 5.1:1, 5.2:1, 5.3:1, 5.4:1, 5.5:1, 5.6:1, 5.7:1, 5.8:1, 5.9:1, 6.0:1, 6.1:1, 6.2:1 or 6.3:1.
[0066] In some optional embodiments, the weight m5 of the carbon nanotubes and the weight m3 of the carbon black particles satisfy the relationship: m5:m3=1:(8.5-10.5);
[0067] In these embodiments, the weight m5 of the carbon nanotubes and the weight m3 of the carbon black particles can satisfy the relationship: m5:m3=1:(8.5-10.5), which can promote the presence of sufficient carbon black particles and carbon nanotubes in the microporous layer. Sufficient carbon black particles and carbon nanotubes can increase the porosity of the microporous layer. In addition, when the divalent chromium ions and the carbon fibers in the base layer form a chromium carbide coating that grows outward, sufficient carbon nanotubes can be connected to the chromium carbide coating to form a network structure of chromium carbides. These network structures of chromium carbides can adjust the porosity and pore size distribution of the microporous layer, thereby increasing the porosity of the gas diffusion layer.
[0068] The weight m5 of the carbon nanotubes and the weight m3 of the carbon black particles may satisfy the relationship: m5:m3=1:8.5, 1:9.0, 1:9.5, 1:10.0 or 1:10.5.
[0069] In some optional embodiments, the heating temperature is 600° C. to 900° C., and the heating time is 0.2 h to 0.5 h;
[0070] In these embodiments, the heating temperature can be 600° C. to 900° C., and the heating time can be 0.2 h to 0.5 h, which can promote the alkaline metal molten salt and the chromium-containing active substance to form a mixed active melt, so as to facilitate the subsequent disproportionation reaction, thereby promoting the mixed active melt to form a chromium carbide anti-corrosion layer of sufficient thickness on the surface of the preheated microporous layer.
[0071] The heating temperature may be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, or 900°C.
[0072] The heating time may be 0.2 h, 0.25 h, 0.3 h, 0.4 h or 0.5 h.
[0073] In some optional embodiments, the cooling end point temperature is ≤30°C;
[0074] In these embodiments, the cooling end temperature is ≤30° C., which can promote the chromium carbide coating formed by the disproportionation reaction to be stably and firmly bonded to the microporous layer, thereby effectively improving the corrosion resistance of the gas diffusion layer.
[0075] Based on a general inventive concept, an embodiment of the present application provides a composite gas diffusion layer with corrosion resistance, and the composite gas diffusion layer is prepared by the preparation method.
[0076] The composite gas diffusion layer is realized based on the above-mentioned preparation method. The specific steps of the preparation method can refer to the above-mentioned embodiment. Since the composite gas diffusion layer adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0077] In some optional embodiments, the composite gas diffusion layer includes a base layer, a microporous layer and an anti-corrosion layer, the microporous layer covers the surface of the base layer, and the anti-corrosion layer covers the surface of the microporous layer;
[0078] In these embodiments, the composite gas diffusion layer may include a base layer, a microporous layer and an anti-corrosion layer, and the microporous layer covers the surface of the base layer, and the anti-corrosion layer covers the surface of the microporous layer, which can enable the anti-corrosion layer to be stably and firmly combined with the microporous layer to effectively improve the corrosion resistance of the gas diffusion layer.
[0079] Figure 2 A schematic flow chart of a method for preparing a composite gas diffusion layer provided in an embodiment of the present application is exemplarily shown;
[0080] Based on a general inventive concept, such as Figure 2 As shown, an embodiment of the present application provides a method for preparing the composite gas diffusion layer, the method comprising:
[0081] S101. The base layer is impregnated with a water repellent solution, and then the impregnated base layer is dried to obtain a pretreated base layer;
[0082] S102. The carbon black particles, carbon nanotubes and pore-forming agent are mixed, and then the mixed mixture is stirred and ultrasonically dispersed to obtain a primary microporous layer slurry;
[0083] S103. The water repellent and the primary microporous layer slurry are mixed, and then the mixed mixture is stirred and ultrasonically dispersed to obtain a microporous layer slurry;
[0084] S104. coating the microporous layer slurry onto the surface of the pretreated substrate layer, and then calcining the pretreated substrate layer coated with the microporous layer slurry to obtain a crude gas diffusion layer;
[0085] S105. Using the preparation method to process the crude gas diffusion layer to obtain a composite gas diffusion layer.
[0086] This method is a method for preparing the above-mentioned composite gas diffusion layer. The specific structure of the composite gas diffusion layer can refer to the above-mentioned embodiment. Since the composite gas diffusion layer adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0087] It should be noted that the stirring time can be 30 minutes, and the ultrasonic dispersion time can be 30 minutes.
[0088] It should be noted that the water repellent in the microporous layer slurry can be polytetrafluoroethylene.
[0089] It should be noted that the stirring and ultrasonic dispersion of the carbon black particles, carbon nanotubes and pore-forming agent can be performed cyclically, and the number of cycles is generally ≥ 4 times.
[0090] It should be noted that the mass ratio of the water repellent content of the microporous layer in the crude gas diffusion layer as a numerator to the microporous layer as a denominator can be 0.15 to 0.30.
[0091] It should be noted that the calcination time can be 2 hours.
[0092] In some optional embodiments, the weight m6 of the water repellent and the weight m5 of the pore forming agent satisfy the relationship: m6:m5=(2.4-3.7):1;
[0093] In these methods, the weight m6 of the hydrophobic agent and the weight m5 of the pore-forming agent can satisfy the relationship: m6:m5=(2.4-3.7):1, which can promote the microporous layer to have a sufficient amount of hydrophobic agent. The sufficient amount of hydrophobic agent can improve the dispersibility of carbon black particles and carbon nanotubes in the microporous layer, so as to promote the carbon black particles and carbon nanotubes to be evenly dispersed in the micropores, so that when the divalent chromium ions and the carbon fibers in the base layer form a chromium carbide coating and grow outward, the chromium carbide coating will also be connected with the carbon nanotubes in the microporous layer to form a network structure of chromium carbide. These network structures of chromium carbides can adjust the porosity and pore size distribution of the microporous layer to avoid the formed chromium carbide coating affecting the porosity of the microporous layer, thereby improving the porosity of the gas diffusion layer.
[0094] The weight m6 of the hydrophobic agent and the weight m5 of the pore-forming agent may satisfy the relationship: m6:m5=2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1 or 3.7:1.
[0095] In some optional embodiments, the drying temperature is 45°C to 55°C, the drying time is 15min to 20min; the immersion time is 5min to 15min;
[0096] In these methods, the drying temperature can be 45°C to 55°C, and the drying time can be 15min to 20min. The water repellent of the base layer can be completely dried by drying to facilitate the subsequent microporous layer slurry to form a microporous layer on the surface of the base layer. In addition, the immersion time can be 5min to 15min, which can promote full contact between the base layer and the water repellent to improve the hydrophobicity of the base layer.
[0097] The drying temperature may be 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C or 55°C.
[0098] The drying time can be 15 min, 16 min, 17 min, 18 min, 19 min or 20 min.
[0099] The immersion time may be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min.
[0100] Based on a general inventive concept, an embodiment of the present application provides a membrane electrode, which includes the composite gas diffusion layer.
[0101] The membrane electrode is realized based on the above-mentioned composite gas diffusion layer. The specific composition of the composite gas diffusion layer can refer to the above-mentioned embodiment. Since the membrane electrode adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0102] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions, or conditions recommended by the manufacturer.
[0103] Example 1
[0104] like Figure 2 As shown, a method for preparing a gas diffusion layer comprises:
[0105] S101. The base layer is impregnated with a water repellent solution, and then the impregnated base layer is dried to obtain a pretreated base layer;
[0106] S102. The carbon black particles, carbon nanotubes and pore-forming agent are mixed, and then the mixed mixture is stirred and ultrasonically dispersed to obtain a primary microporous layer slurry;
[0107] S103. The hydrophobic agent and the primary microporous layer slurry are mixed, and the mixed mixture is stirred and ultrasonically dispersed to obtain a microporous layer slurry; the mass ratio of the solute in the hydrophobic agent as the numerator and the solvent in the hydrophobic agent as the denominator is 0.11;
[0108] S104. coating the microporous layer slurry onto the surface of the pretreated substrate layer, and then calcining the pretreated substrate layer coated with the microporous layer slurry to obtain a crude gas diffusion layer;
[0109] S105. Using the preparation method to process the crude gas diffusion layer to obtain a composite gas diffusion layer.
[0110] The preparation method used in step S105 includes:
[0111] S1. The alkaline metal molten salt and the chromium-containing active substance are mixed to obtain a mixed active alkaline metal molten salt;
[0112] S2. preheating the microporous layer to obtain a preheated microporous layer;
[0113] S3. Heating the mixed active alkaline metal molten salt in a vacuum environment to obtain a mixed active melt;
[0114] S4. Using nickel wire as a support, immersing the preheated microporous layer into the mixed active melt to perform a disproportionation reaction to obtain a crude composite gas diffusion layer having an anti-corrosion coating;
[0115] S5. Lift the nickel wire support to cool the crude composite gas diffusion layer having an anti-corrosion coating, and then purify it to obtain a composite gas diffusion layer;
[0116] The raw material of the microporous layer includes carbon nanotubes, and the raw material of the base layer includes carbon fibers;
[0117] The weight m1 of different alkaline metal molten salts and the weight m2 of chromium-containing active substances (m1:m2=8:1, 7.2:1 and 3:1) are mixed in a mass ratio of 1:1:1 so that the final weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance satisfy the relationship: m1:m2=18.2:3.
[0118] The chromium-containing active substance includes metallic chromium and chromium fluoride, and the amount n1 of metallic chromium and the amount n2 of chromium chloride satisfy the relationship: n1:n2=9:1; the alkaline metal molten salt is sodium chloride and potassium chloride, and the amount n3 of sodium chloride and the amount n4 of potassium chloride satisfy the relationship: n3:n4=1:1.
[0119] The raw materials of the microporous layer also include carbon black particles and pore-forming agents. The weight m3 of the carbon black particles, the weight m4 of the carbon nanotubes and the weight m5 of the pore-forming agent satisfy the relationship: (m3+m4):m5=5.0:1.
[0120] The weight m5 of the carbon nanotubes and the weight m3 of the carbon black particles satisfy the relationship: m5:m3=1:8.5.
[0121] The heating temperature is 900°C and the heating time is 0.3h.
[0122] The cooling end temperature is 30℃
[0123] The weight m6 of the water repellent and the weight m5 of the pore former satisfy the relationship: m6:m5=3.0:1.
[0124] The drying temperature was 50°C, the drying time was 15 min, and the immersion time was 5 min.
[0125] Example 2
[0126] Based on the contents disclosed in Example 1, the following modifications are further made:
[0127] The weight m1 of different alkaline metal molten salts and the weight m2 of chromium-containing active substances (m1:m2=8:1, 7.2:1 and 3:1) are mixed in a mass ratio of 1:1:1 so that the final weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance satisfy the relationship: m1:m2=18.2:3.
[0128] The chromium-containing active material includes metallic chromium and / or chromium fluoride, and the alkaline metal molten salt includes alkaline metal chloride.
[0129] The chromium-containing active substance includes metallic chromium and chromium fluoride, and the amount n1 of metallic chromium and the amount n2 of chromium chloride satisfy the relationship: n1:n2=9:1; the alkaline metal molten salt is sodium chloride and potassium chloride, and the amount n3 of sodium chloride and the amount n4 of potassium chloride satisfy the relationship: n3:n4=1.2:1.
[0130] The raw materials of the microporous layer also include carbon black particles and pore-forming agents. The weight m3 of the carbon black particles, the weight m4 of the carbon nanotubes and the weight m5 of the pore-forming agent satisfy the relationship: (m3+m4):m5=4.7:1.
[0131] The weight m5 of the carbon nanotubes and the weight m3 of the carbon black particles satisfy the relationship: m5:m3=1:9.
[0132] The heating temperature is 850°C and the heating time is 0.3h.
[0133] The cooling end point temperature was 30°C.
[0134] The weight m6 of the water repellent and the weight m5 of the pore former satisfy the relationship: m6:m5=2.5:1.
[0135] The drying temperature was 50°C, the drying time was 15 min, and the immersion time was 5 min.
[0136] Example 3
[0137] Based on the contents disclosed in Example 1, the following modifications are further made:
[0138] The weight m1 of different alkaline metal molten salts and the weight m2 of chromium-containing active substances (m1:m2=8:1, 7.2:1 and 3:1) are mixed in a mass ratio of 1:1:1 so that the final weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance satisfy the relationship: m1:m2=18.2:3.
[0139] The chromium-containing active substance includes metallic chromium and chromium fluoride, and the amount n1 of metallic chromium and the amount n2 of chromium chloride satisfy the relationship: n1:n2=9:1; the alkaline metal molten salt is sodium chloride and potassium chloride, and the amount n3 of sodium chloride and the amount n4 of potassium chloride satisfy the relationship: n3:n4=1.2:1.
[0140] The raw materials of the microporous layer also include carbon black particles and pore-forming agents. The weight m3 of the carbon black particles, the weight m4 of the carbon nanotubes and the weight m5 of the pore-forming agent satisfy the relationship: (m3+m4):m5=6.0:1.
[0141] The weight m5 of the carbon nanotubes and the weight m3 of the carbon black particles satisfy the relationship: m5:m3=1:10.
[0142] The heating temperature is 800°C and the heating time is 0.3h.
[0143] The cooling end point temperature was 30°C.
[0144] The weight m6 of the water repellent and the weight m5 of the pore former satisfy the relationship: m6:m5=3.5:1.
[0145] The drying temperature was 50°C, the drying time was 15 min, and the immersion time was 10 min.
[0146] Comparative Example 1
[0147] Based on the contents disclosed in Example 1, the following modifications are further made:
[0148] No mixed active alkaline metal molten salt is used to form the anti-corrosion layer.
[0149] After obtaining the microporous layer slurry, the microporous layer slurry is coated on the surface of the pretreated substrate layer by screen printing, and then the pretreated substrate layer coated with the microporous layer slurry is taken out and placed in an oven for drying. The drying procedures are as follows: first drying at 60°C for 5 minutes, then drying at 80°C for 5 minutes, and then drying at 100°C for 5 minutes. Finally, the dried pretreated substrate layer is placed in a box-type resistance furnace and heated to 300°C and kept warm for 0.5 hours to obtain the final gas diffusion layer.
[0150] Comparative Example 2
[0151] Based on the contents disclosed in Example 1, the following modifications are further made:
[0152] The weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance satisfy the relationship: m1:m2=3:1.
[0153] Comparative Example 3
[0154] Based on the contents disclosed in Example 1, the following modifications are further made:
[0155] The weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance satisfy the relationship: m1:m2=15:1.
[0156] Comparative Example 4
[0157] Based on the contents disclosed in Example 1, the following modifications are further made:
[0158] The heating temperature is 500°C and the heating time is 0.3h.
[0159] Comparative Example 5
[0160] Based on the contents disclosed in Example 1, the following modifications are further made:
[0161] The heating temperature is 950°C and the heating time is 0.3h.
[0162] Related experiments and effect data:
[0163] The gas diffusion layers obtained in the embodiments and comparative examples were tested, and the porosity before and after the anti-corrosion coating treatment was statistically analyzed. The results are shown in Table 1.
[0164] Table 1 Porosity changes of various embodiments and comparative examples before and after anti-corrosion coating treatment
[0165]
[0166]
[0167] As can be seen from Table 1, the method for preparing a corrosion-resistant composite gas diffusion layer provided in an embodiment of the present application is to obtain a sufficient amount of divalent chromium ions by a disproportionate reaction of alkaline metal molten salt and chromium-containing active material on the surface of the microporous layer. The sufficient amount of divalent chromium ions can be effectively diffused into the microporous layer and the base layer, and form chromium carbide coatings with the carbon nanotubes in the microporous layer and the carbon fibers in the base layer, respectively. These chromium carbide coatings can achieve the simultaneous improvement of the corrosion resistance and porosity of the composite gas diffusion layer.
[0168] In addition, the polarization curves of the composite gas diffusion layer were tested for the gas diffusion layers obtained in Example 1, Example 2 and Comparative Example 1. The results are as follows: Figure 3 and Figure 4 shown.
[0169] Figure 3 A schematic diagram showing a comparison of initial performance polarization curves of the composite gas diffusion layers provided in Example 1, Example 2 and Comparative Example 1 of the present application is exemplarily shown;
[0170] Figure 4 A schematic diagram showing a comparison of performance polarization curves of the composite gas diffusion layers provided in Example 1, Example 2 and Comparative Example 1 of the present application after 100 hours of durability treatment is exemplarily shown;
[0171] like Figure 3 and Figure 4 As shown, the initial performance of the composite gas diffusion layer obtained in Example 1 is 0.59V@2000mA / cm 2 , while the initial performance of the composite gas diffusion layer obtained in Example 2 is 0.57V@2000mA / cm 2 The initial performance of the gas diffusion layer obtained in comparative example 1 is 0.54V@2000mA / cm 2 After 100 hours of durability treatment, the durability performance of the composite gas diffusion layer obtained in Example 1 is 0.58V@2000mA / cm 2 The performance of the composite gas diffusion layer obtained in Example 2 after durability treatment is 0.55V@2000mA / cm 2 The performance of the composite gas diffusion layer obtained in Example 1 after durability treatment is 0.5V@2000mA / cm 2This indicates that the performance of the composite gas diffusion layer obtained in Comparative Example 1 is greatly reduced after the durability treatment, indicating that after the durability treatment under the same working conditions, the gas diffusion layer samples without anti-corrosion coatings such as Comparative Example 1 are very likely to have carbon corrosion, and the composite gas diffusion layer with carbon corrosion will greatly affect the overall mechanical strength and pore structure of the gas diffusion layer, resulting in a decrease in the water vapor transmission capacity of the gas diffusion layer. The composite gas diffusion layers obtained in Examples 1 and 2 have a smaller performance reduction after the durability treatment, and by controlling the amount of carbon nanotubes added, a composite gas diffusion layer with better pore size distribution and porosity can be prepared; and under the same durability treatment conditions, the performance of the composite gas diffusion layer of Example 1 is more excellent.
[0172] In summary, the embodiment of the present application provides a method for preparing a corrosion-resistant composite gas diffusion layer, in which an alkaline metal molten salt and a chromium-containing active substance undergo a disproportionation reaction on the surface of a microporous layer to obtain a sufficient amount of divalent chromium ions. A sufficient amount of divalent chromium ions can achieve a simultaneous improvement in the corrosion resistance and porosity of the composite gas diffusion layer.
[0173] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.
Claims
1. A method for preparing a composite gas diffusion layer with corrosion resistance, the method for preparing a crude gas diffusion layer, the crude gas diffusion layer comprising a base layer and a microporous layer covering the surface of the base layer, characterized in that: The preparation method comprises: Mixing alkaline metal molten salt and chromium-containing active material to obtain mixed active alkaline metal molten salt; preheating the microporous layer to obtain a preheated microporous layer; Heating the mixed active alkaline metal molten salt in a vacuum environment to obtain a mixed active melt; immersing the preheated microporous layer in the mixed active melt to perform a disproportionation reaction to obtain a crude composite gas diffusion layer with an anti-corrosion coating; Cooling the crude composite gas diffusion layer with the anti-corrosion coating and then purifying it to obtain a composite gas diffusion layer; Wherein, the raw material of the microporous layer includes carbon nanotubes, and the raw material of the base layer includes carbon fibers; The weight m1 of the alkaline metal molten salt and the weight m2 of the chromium-containing active substance satisfy the relationship: m1:m2=(5:1)-(10:1).
2. The preparation method according to claim 1, characterized in that: The chromium-containing active material includes metallic chromium and / or chromium fluoride, and the alkaline metal molten salt includes a chloride salt of an alkaline metal.
3. The preparation method according to claim 2, characterized in that: The chromium-containing active material includes metallic chromium and chromium chloride, and the amount n1 of the metallic chromium and the amount n2 of the chromium chloride satisfy the relationship: n1:n2≥8:
1.
4. The preparation method according to claim 2, characterized in that: The alkaline metal includes sodium and / or lithium.
5. The preparation method according to claim 1, characterized in that: The raw materials of the microporous layer also include carbon black particles and pore-forming agents. The weight m3 of the carbon black particles, the weight m4 of the carbon nanotubes and the weight m5 of the pore-forming agent satisfy the relationship: (m3+m4):m5=(4.7-6.3):
1.
6. The preparation method according to claim 5, characterized in that: The weight m5 of the carbon nanotubes and the weight m3 of the carbon black particles satisfy the relationship: m5:m3=1:(8.5-10.5).
7. The preparation method according to claim 1, characterized in that: The heating temperature is 600° C. to 900° C., and the heating time is 0.2 h to 0.5 h.
8. The preparation method according to claim 1, characterized in that: The cooling end point temperature is ≤30°C.
9. A composite gas diffusion layer having corrosion resistance, characterized in that: The composite gas diffusion layer is prepared by the preparation method according to any one of claims 1 to 8.
10. The composite gas diffusion layer according to claim 9, characterized in that: The composite gas diffusion layer comprises a base layer, a microporous layer and an anti-corrosion layer. The microporous layer covers the surface of the base layer, and the anti-corrosion layer covers the surface of the microporous layer.
11. A method for preparing the composite gas diffusion layer according to claim 9 or 10, characterized in that: The method comprises: The base layer is impregnated with a water repellent solution, and then the impregnated base layer is dried to obtain a pre-treated base layer; The carbon black particles, carbon nanotubes and pore-forming agent are mixed, and then the mixed mixture is stirred and ultrasonically dispersed to obtain a primary microporous layer slurry; Mixing the water repellent and the primary microporous layer slurry, and then stirring and ultrasonically dispersing the mixed mixture to obtain a microporous layer slurry; Applying the microporous layer slurry to the surface of the pretreated substrate layer, and then calcining the pretreated substrate layer coated with the microporous layer slurry to obtain a crude gas diffusion layer; The crude gas diffusion layer is processed using the preparation method according to any one of claims 1 to 8 to obtain a composite gas diffusion layer.
12. The method according to claim 11, characterized in that The weight m6 of the water repellent and the weight m5 of the pore forming agent satisfy the relationship: m6:m5=(2.4-3.7):
1.
13. The method according to claim 11, characterized in that The drying temperature is 45° C. to 55° C., the drying time is 15 min to 20 min, and the immersion time is 5 min to 15 min.
14. A membrane electrode, characterized in that: The membrane electrode comprises the composite gas diffusion layer according to claim 9 or 10.